PENGEMBANGAN BANK SAMPAH DAHLIA DEMI MENYELAMATKAN BUMI INDONESIA - Hotib Burohman; Elsa Regita Cahyani; Yulita Pujiharti; Loesita Sari; Budijanto Budijanto (JPM PAMBUDI, 2023)
The activity of a waste bank in Kedung Village Giri Purno formed a waste bank named "DAHLIA WASTE BANK". In addition to the economic benefits, where from waste savings one gets money to pay for electricity and buy groceries, environmental health is also realized, with community conditions that are cleaner, greener, more comfortable, and healthier. Integrated waste management can stimulate creativity and innovation from the community so as to improve people's welfare. First, the local government takes an approach to the surrounding community and stakeholders. In implementing citizen education by developing a waste bank, intensive coordination must be carried out with PKK administrators in every activity that will be carried out so that citizen empowerment becomes more optimal, basically the local government is trying to continue to develop this waste bank so that later it can continue to grow. the economy is getting better in the future so that the presence of a garbage bank has encouraged capacity building for residents by seeking the formation of self-reliance and self-sufficiency of citizens